PENGARUH BRAND IMAGE TERHADAP KEPERCAYAAN KONSUMEN DAN KEPUTUSAN PEMBELIAN PRODUK UMKM DI KOTA KENDARI - Dzulfikri Azis Muthalib (Jurnal Multidisipliner Bharasumba, 2026)
This study aims to analyze the effect of brand image on consumer trust and purchasing decisions of MSME products in Kendari City, Southeast Sulawesi, as well as to examine the mediating role of consumer trust. This research employs a quantitative approach with an explanatory design. Data were collected through a survey of 175 MSME consumers in Kendari City selected using purposive sampling. Data analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0 software. The research instruments were adapted from validated measurement scales, with all constructs meeting the criteria for reliability and validity. The results indicate that brand image has a positive and significant effect on consumer trust and purchasing decisions. Furthermore, consumer trust also has a positive and significant effect on purchasing decisions. Further findings reveal that consumer trust partially mediates the relationship between brand image and purchasing decisions, indicating that brand image influences purchasing decisions both directly and indirectly through the mechanism of trust formation..